1994
DOI: 10.1016/0045-6535(94)90084-1
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro influence of the burrowing polychaete Nereis diversicolor on the fate of petroleum hydrocarbons in marine sediments

Abstract: International audienceThe in vitro fate of the saturated hydrocarbon fraction (SF) of Arabian Light crude oil has been studied in PVC cores filled with a coastal marine sediment defaunated by sieving. Experiments were conducted in absence or presence of polychaetes Nereis diversicolor. The luminophore tracer technique was used to quantify the mixing of sediment by worms. Presence of crude oil reduced the building of burrows by polychaetes. This work demonstrates the ability of infaunal organisms to stimulate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 20 publications
3
28
0
Order By: Relevance
“…In this way, sedimentadsorbed contaminants remain in contact with the overlying water for longer periods of time than in nonbioturbated sediment (Reynoldson 1987), thus enhancing the diffusive loss of contaminants from the sediment to the water. Also, burrowing enhances the surface sediment area which, together with irrigation, increases the diffusive loss of contaminants from the sediment (Gilbert et al 1994). Furthermore, the aerobic microbial community may be stimulated by irrigation and burrowing activity of tube-dwelling organisms as penetration of oxygen increases, thereby enhancing aerobic zones in sediments (Krantzberg 1985).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, sedimentadsorbed contaminants remain in contact with the overlying water for longer periods of time than in nonbioturbated sediment (Reynoldson 1987), thus enhancing the diffusive loss of contaminants from the sediment to the water. Also, burrowing enhances the surface sediment area which, together with irrigation, increases the diffusive loss of contaminants from the sediment (Gilbert et al 1994). Furthermore, the aerobic microbial community may be stimulated by irrigation and burrowing activity of tube-dwelling organisms as penetration of oxygen increases, thereby enhancing aerobic zones in sediments (Krantzberg 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been demonstrated that bioturbation can have a significant impact on the burial and degradation of sedimentary lipid components (e.g. Gilbert et al, 1994Gilbert et al, , 1996Sun et al, 1999;Ingalls et al, 2000;Grossi et al, 2002Grossi et al, , 2003, the influence of redox oscillation on lipid degradation has been little studied. Using a diffusively ''open'' incubation sedimentary system that mimics varying conditions of oxygenation in bioturbated sediments, Sun et al (1993) showed that redox changes influenced the diagenetic pathways of chloropigments.…”
Section: Introductionmentioning
confidence: 99%
“…However, this polychaete causes substantial changes in oxygenation and redox potential of surficial and burrow-lining sediments that may have a significant effect on the bacterial assemblages (Esselink & Zwarts 1989, Gilbert et al 1994. For instance, denitrification rates increased in surface sediments with H. diversicolor colonies and activity of chemolithotrophic bacteria was stimulated in burrows (Gilbert et al 1994). Lucas & Bertru (1997) demonstrated that > 80% of ingested sediment bacteria disappeared in the H. diversicolor midgut (MG) via bacteriolysis.…”
Section: Introductionmentioning
confidence: 99%